Financial technology platforms and enhancing SME financing in Jordan - Anas Ahmad Bani Atta (Discover Sustainability)
Abstract Purpose This study investigates the impact of financial technology (fintech) platform in enhancing access to finance for small and medium enterprises’ (SMEs) in Jordan. Design/methodology A mixed-methods design using an ex-post facto survey method. Primary data were collected from 383 SME owners via Google Forms distributed through WhatsApp and email. The study utilized snowball sampling and statistical analysis including Pearson’s correlation and multiple regression to examine relationships between fintech usage and access to finance. Results The findings demonstrate that fintech platforms significantly optimize SMEs’ access to finance and encourage financial inclusion. Contributions from fintech platforms and financial inclusion factors were important predictors of financing access, but challenges and adoption barriers had no significant impact. Implications The study highlights the possibility of fintech to causeway financing gaps for SMEs in Jordan. It recommends that SME owners implement fintech instruments to improve financial management and credit access, whereas policymakers should encourage fintech adoption through digital literacy, cybersecurity regulation, and supportive policy frameworks. Originality/value This study is one of the few to empirically show the constructive role of fintech solutions for SME financing in Jordan. It provides novel insights into how fintech platforms can drive financial inclusion and economic development in emerging markets.